DYNAMIC DESCRIPTIONS OF SHOCK INSTRUMENT FOR LIQUIDATION OF GRABBINGS OF BORING COLUMN - Мойсишин, Василь Михайлович; Левчук, Катерина Григорівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The mathematical model of compatible work of the talevoi system, boring column and shock mechanism is developed. At the design the wave phenomena are taken into account in boring pipes. The numerical calculation of dynamic descriptions (time of acceleration, duration of blow, coefficient of renewal, acquired and lost kinetic energies of emergency arrangement) which arise up at work of lock pair is conducted. Engineering is given the base of getting results of computer decisions.